The Impact of Fear of Missing Out (FoMO) and Materialism on Financial Stress Among Students at Public Universities: The Moderating Role of Religiosity - Ratna Nurani; M. Munawar Ansyori; Thi Kim Anh Vu; Muhammad Firmansyah; Jose Antonio Lopez Castro (Yayasan Pendidikan Islam Al-Matani, 2026)
This study aims to examine the effects of Fear of Missing Out (FOMO) and materialism on college students’ financial stress and to analyze the moderating role of religiosity in these relationships. The study was motivated by the increasing influence of digital lifestyles and consumerist behavior among college students, as well as the limited empirical studies integrating psychological and spiritual factors into a comprehensive framework. A quantitative approach was employed involving 200 students from a state university in Pekanbaru City selected through purposive sampling. Data were collected using a structured questionnaire based on a Likert scale and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that FOMO and materialism have a positive and significant effect on students’ financial stress, indicating that higher levels of social comparison and material-oriented values contribute to greater financial pressure. Furthermore, religiosity moderates the effects of FOMO and materialism by weakening their influence on financial stress. These results suggest that psychological factors play a dominant role in generating financial stress, while religiosity serves as a coping mechanism that helps students manage financial challenges. This study contributes to the financial psychology literature by integrating behavioral, cognitive, and spiritual dimensions and offers practical implications for value-based financial literacy and responsible consumer behavior among students.